Tyrone Hayes & Penelope Jagessar Chaffer | The Toxic Baby - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Filmmaker Penelope Jagessar Chaffer was curious about the chemicals she was exposed to while pregnant: Could they affect her unborn child? So she asked scientist Tyrone Hayes to brief her on one he studied closely: atrazine, a herbicide used on corn. (Hayes, an expert on amphibians, is a critic of atrazine, which displays a disturbing effect on frog development.) Onstage together at TEDWomen, Hayes and Chaffer tell their story. This talk was presented at an official TED conference,